Analisis Preferensi dan Pengalaman Pengguna Terhadap Inovasi Layanan Cicil Emas di BSI KCP Jepara Guna Merumuskan Strategi Peningkatan Kualitas Layanan - Nurmaila Febriana Nashwa; miswan ansori; Imron Choeri (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze user preferences and experiences regarding the Gold Installment service innovation at Bank Syariah Indonesia (BSI) Jepara Branch Office as a basis for formulating a service quality improvement strategy. The study used a qualitative descriptive approach with a field research method. Research informants consisted of bank management and customers who use the Gold Installment service. Data were collected through observation, in-depth interviews, and documentation, then analyzed using an interactive model that includes data reduction, data presentation, and drawing and verifying conclusions. The results show that customer preferences in choosing the Gold Installment service are influenced by trust in the sharia label and murabahah contract as well as consideration of brand strength. Most customers tend to choose Antam Gold over BSI Gold because they consider liquidity and ease of transactions. From a user experience aspect, the BYOND by BSI digital application is considered to provide easy access to services, although there are still technical obstacles and limited education about the product. Based on these findings, the service quality improvement strategy is directed at optimizing digital features, strengthening product education, and accelerating the service process structurally.